Implementasi Konsep Nostlagic Getaway pada Perancangan Interior â€œSurabaya Senior Sport Centreâ€ - Limbang, Jessica (Intra, 2016)
Physical exercise and group activity are some of the ways that can improve this elderlyâ€™s quality of life. However, in Surabaya, the number of facilities that are proper and suitable for the elderly is still lacking. Designing physical exercise facility for the elderly should emphasize safety and comfort. More than that, it is also expected that the facility could contribute positively to their physical and social condition. This project used Bryan Lawsonâ€™s method for design thinking. The concept, â€œNostlagic Getawayâ€, is expected be the answer to fulfill the user needs. This concept has few of implementation points like lighting, flooring, wayfinding, style, view, user safety, area of rest, layout, emergency help, and color and materials, are hope to be a solution for many safety and comfortablity problems and user experience in this facilities. Therefore, it is expected that the designed facility could answer the needs of the targeted user and welcomed positively by the society.